Improving the tensile properties of 3D printed PLA by optimizing the processing parameter - Nugroho, Aris Widyo; Budiantoro, Cahyo (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2019)
Low-cost desktop 3D printing is now dominated by free and open source self-replicating rapid prototype. However, optimum printing process parameters have not been provided by the manufacturer, since there are several process parameters that need to be optimized to obtain acceptable dimension error and strength properties. This paper aims to present the optimum process parameters for the 3D printing process of Polylactic Acid (PLA) part using Taguchi Method. A specimen standard of ASTM D638 Type IV made of biodegradable polymer, PLA, has been used as a tensile strength test to represent printed part quality. Four printing process parameters: temperatures, extrusion width, infill density and infill pattern have been optimized using Taguchi Methods.  Test was carried out to find the highest tensile strength based on the optimum parameter setting and validated them with experiment. The result shows that the tensile strength response was predominantly influenced by infill density followed by nozzle temperature, infill pattern and extrusion width.  The optimum level setting was obtained at 75% of infill density (C3), 215oC of nozzle temperature (A3), honeycomb infill (D1) and 0.3 mm of extrusion width (B1). At optimized parameters the tensile strength PLA parts significantly was found of 30.52 MPa at a confidence interval of 95%.